Implementasi Program Desa Cerdas di Desa Pandau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Khotami; Rahmawati, Ira (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
This study aims to analyze the implementation of the Smart Village program in realizing smart governance in Pandau Jaya Village, Siak Hulu District, Kampar Regency. This study employs the Van Meter and Van Horn policy implementation theory, which consists of six variables: policy standards and objectives, resources, characteristics of implementing organizations, inter-organizational communication, implementer disposition, and the social, economic, and political environment. The research method used is a qualitative approach, with data collected through observation, interviews, and documentation. The research informants consist of village officials and community members as service users, selected purposively based on their involvement in the program implementation. The results indicate that the implementation of the Smart Village program has been running quite well, particularly in terms of the clarity of program objectives and technological support. However, several obstacles remain, such as low digital literacy among the community, limited human resources, and suboptimal program communication. This program has had a positive impact on improving the effectiveness, efficiency, and transparency of public services, as well as facilitating easier access to administrative services for the community. Therefore, it is necessary to enhance human resource capacity and strengthen program socialization to ensure more optimal and sustainable implementation.